Avaliação do desajuste vertical de infraestrutura para confecção de próteses totais mandibulares sobre implantes obtidas por CAD-CAM - Amaral, Wilson Silva (2015)
The construction process of infrastructures by casting method was long considered the gold standard in dentistry. As well as the technique had a lot of evolution, the industry accompanied such process. Best results were obtained and consequently more predictability were achieved. Cad Cam technology comes to dentistry and revolutionizes the workflow of the dental prosthesis laboratories. This work has the objective to analyze adaptation accuracy comparative form of three different methods of preparation of infrastructure for implant-supported mandibular total prosthesis. Groups: titanium milled bars (TMB) free of casting or overcasting; overcasted bars (OCB) group, which used metal based cylinders and casted Group (WC) which the bars were milled in wax and casted later. As the most positive result, the TMB group presented better adaptation with 2.02 µm average. Followed by the OCB group with 7.06 µm of average. At last the WC group with average of 15.8 µm. Despite of the statistically significancy, all results are within the acceptable clinically